(3GdHfhc GdJLGQjI hGdJShjb GdeUQaj (B/s - (3LdOI, SGeQs ((3YeGf(B: s (3OGQ GSGeI(B, s, 2009)
(3eGgjI GdHfhc GdJLGQjI, fTGW hCfhGY GdHfhc GdJLGQjI, YdGbI GdHfhc GdJLGQjI HGdHfc GdeQcRj, GOGQI GdSjhdI GdeUQajI, GdGSJQGJjLjGJ GdCSGSjI dEOGQI hLPH GdhOGFY GdeUQajI, CSGSjGJ efM GdbQhV hGdGFJeGf, HYV GdGJLGgGJ GdMOjKI aj eLGd GdNOeI GdeUQajI, GdJMdjd GdeGdj(B...(3GWGQ YGe, GdQbGHI Ydi GdCOGA GdYGe ddHfc, GdJShjb GdeUQaj hGdNOeGJ GdeUQajI, TQcGJ GdJCejf hGdHfhc GdGSdGejI, GdHfhc GdGdcJQhfjIs
(3HHdjhZQGajG(B: (3U(B.253-256s
Keywords: (3GdGbJUGO GdeGdjs; (3GdHfhc GdGSdGejIs; (3GdHfhc GdJLGQjIs; (3GdJShjbs